(untitled) (Eurasian Medical Research Periodical, 2023)
Differential diagnosis of the etiology of phthisis is an urgent problem in phthisiology. The study made it possible to establish, for the purpose of differential diagnosis of leaks, to establish tuberculous etiology, in addition to traditional research methods, use Diaskintest [out of 24, 16 (66.6%) gives a positive result], in patients with a negative and dubious Mantoux test. The performed analysis of discharge from the congestion using the GeneXpert Rif method in patients with a negative smear result by bacterioscopy in 53.5% allows us to detect tuberculosis, and patients with drug-resistant tuberculosis begin adequate complex therapy. The most frequently aggravated complications were tuberculous spondylitis in 34 patients with coxitis in 12 patients and tuberculosis of peripheral lymph nodes in 11 patients.